Morning sky [large type] - Miller, Judith, 1944- (Miller, Judith, 1944- Freedom's path, 2008)
"Ezekiel Harban carries bitterness and suspicion toward his wife's half-sister. Lilly recently fled New Orleans and moved to his Kansas prairie. He is sure she is hiding something, but what?"--Provided by publisher.